2020
DOI: 10.2106/jbjs.st.19.00042
|View full text |Cite
|
Sign up to set email alerts
|

Open Hip Abductor Tendon Repair into a Bone Trough

Abstract: Background: Hip abductor tendon tears are a well-recognized entity that results in progressive lateral hip pain, weakness, and limping. These can occur in patients with native hips or in patients following total hip arthroplasty. However, treatment of these 2 distinct groups does not differ. We describe a new repair technique utilizing a longitudinal bone trough in the greater trochanter. We compare our results (focusing on gluteus medius tendon avulsions) and traditional repair with suture anchors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Most published literature reports cohorts of <30 patients analysing IR or <24 cases studying THA+repairs, with a follow-up <1 year, 1,5,1417 and the most comprehensive series report different repair methods and outcomes. 2,6,7,18 Despite disparities, most demonstrate improvement in PROMs after IR and THA+repair, 69,1418 which is in line with our findings. Studies reporting VAS pain scores in both groups report an average result of 1.8–2.2.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most published literature reports cohorts of <30 patients analysing IR or <24 cases studying THA+repairs, with a follow-up <1 year, 1,5,1417 and the most comprehensive series report different repair methods and outcomes. 2,6,7,18 Despite disparities, most demonstrate improvement in PROMs after IR and THA+repair, 69,1418 which is in line with our findings. Studies reporting VAS pain scores in both groups report an average result of 1.8–2.2.…”
Section: Discussionsupporting
confidence: 91%
“…1,4 Over the last decade, studies have been published analysing gluteal tendon tears and their management. [5][6][7][8][9][10][11][12][13][14][15] There is growing evidence that where conservative treatment fails, surgical repair is an effective and safe treatment. 1,5 Nevertheless, most published studies consist of small cohorts, lack definition of the type of tears, complications, re-tears, and report follow-up periods shorter than 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…Nine patients had good results with strong postoperative abduction and no limp, whereas 1 patient had weak abduction and a slight limp and 1 with a severe limp. Incavo and Harper described a technique in which the abductors are repaired through a vertical bone trough rather than a suture anchor or transosseous repair 14 . We have found that one of the challenges with these techniques can be reliable and robust distal fixation to the femur, which led to the modification using augmentation with mesh and distal fixation with cerclage cable.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating the impact of these changes, 1 metric to assess the value of an article is the interest that it generates. For that, we also present the top-10 most viewed JBJS Essential Surgical Techniques articles 3-12 . Although the frequency with which a procedure is performed plays a role in the viewership metrics, all of these articles are outstanding examples of the high-quality content we aim to provide.…”
mentioning
confidence: 99%
“…• Migrating from a largely written article to an all-video, online format featuring an enhanced abstract • Adding English-language captioning to broaden outreach internationally and provide greater accessibility When evaluating the impact of these changes, 1 metric to assess the value of an article is the interest that it generates. For that, we also present the top-10 most viewed JBJS Essential Surgical Techniques articles [3][4][5][6][7][8][9][10][11][12] . Although the frequency with which a procedure is performed plays a role in the viewership metrics, all of these articles are outstanding examples of the high-quality content we aim to provide.…”
mentioning
confidence: 99%